The Boss Baby : Family business - McGrath, Tom, 1964-; Hermann, Jeff; McCullers, Michael; Baldwin, Alec, 1958-; Marsden, James, 1973-; Sedaris, Amy; Greenblatt, Ariana, 2007-; Goldblum, Jeff, 1952-; Longoria, Eva, 1975-; McGrath, James (James Francis Thomas); Kimmel, Jimmy, 1967-; Kudrow, Lisa; et al. (Universal City, CA Universal Studios, 2021)
Now adults, Theodore Templeton and his estranged brother take a magical formula that transforms them into babies for 48 hours. Together, they must now go undercover to prevent an evil genius from turning fellow toddlers intro monstrous brats.
Originally released as a motion picture in 2021.
Based on the books by Marla Frazee.
Title from container.
Widescreen (2.39:1)
Bonus features: all new original short, "Precious Templeton: a pony tale"; deleted scene with intro by director Tom McGrath; Never grow up: the big babies behind The Boss Baby: Family Business; Roll call; Creative experiment lab; Boss Baby art class: how to draw; "Together we stand" lyric video; feature commentary with director/executive producer Tom McGrath, producer Jeff Hermann and production designer Raymond Zibach.
Music by Hans Zimmer and Steve Mazzaro ; editors, Mary Blee, Mark Hester.
Keywords: Infants -- Juvenile drama; Supervisors -- Juvenile drama; Brothers -- Juvenile drama; Nieces -- Juvenile drama; DVDs; Action and adventure films; Animated films; Children's films; Comedy films; Computer animation films; Drama; Feature films; Fiction films; Film adaptations; Video recordings for people with visual disabilities; Video recordings for the hearing impaired